(untitled) (Baghdad Science Journal, 2024)
Urine samples had been gathered from females living in Baghdad city. The sample consisted of 30 females who suffered from U.T.I (Urinary tract infections) and 20 healthy females. The type of urine U.T.I was specified by the emergency lab in Al-Kindy hospital, and alpha tracks were determined by the nuclear track detector CR-39. The concentrations of alpha in 30 urine samples taken from females who had U.T.I ranged from 0.327ppm-1.583ppm, with an average of 0.94965 ppm. The maximum value 1.583 ppm is belonging to females with an aged 57 years old. The results of healthy female concentration ranged from 0.022 ppm-0.459ppm with an average of (0.30855ppm). The findings revealed that alpha emitter concentrations differed from woman to woman, depending on the degree to which women’s bodies were allergic to the radiation, according to their age. The finding revealed of patient female had higher concentrations than healthy females